Impaired response to sleep deprivation in heterozygous Disc1 mutant mice. (2nd January 2022) - Tsao, Chih-Yu; Tuan, Li-Heng; Lee, Lukas Jyuhn-Hsiarn; Liu, Chih-Min; Hwu, Hai-Gwo; Lee, Li-Jen
Abstract: Objectives: Sleep/circadian rhythm disturbances are environmental stress factors that might interact with genetic risk factors and contribute to the pathogenesis of psychiatric disorders. Methods: In this study, the multiple-platform method was used to induce sleep deprivation (SD). We evaluated the impact of 72-hour SD in behavioural, anatomical, and biochemical aspects in heterozygous Disc1 mutant ( Disc1 Het) mice, an animal model of schizophrenia. Results: The sleep pattern and circadian activity were not altered in Disc1 Het mice. Yet, we observed differential responses to SD stress between genotypes. Increased microglial density and reduced neuronal proliferative activity were found in the dentate gyrus, a neurogenic niche, in Het-SD mice. Notably, SD-induced Bdnf mRNA elevations were evident in both WT and Het mice, while only in WT-SD mice did we observe increased BDNF protein expression. Our results suggested an SD-induced physical response featured by the elevation of BDNF protein expression to counteract the harmful influences of SD and sufficient DISC1 is required in this process. Conclusions: The present study proposes that sleep disturbance could be pathogenic especially in genetically predisposed subjects who fail to cope with the stress. Potential therapeutic strategies for psychiatric disorders targeting the mRNA translation machinery could be considered.